Case Report: Neo-ostium creation with saphenous vein in a patient with anomalous origin of the right coronary artery - Temur, Bahar; Özcan, Zeynep Sıla; Başgöze, Serdar; Aydın, Selim; Güzelmeriç, Füsun; Erek, Ersin (Frontiers in Pediatrics, 2023)
Anomalous origin of the right coronary artery from left sinus of valsalva is a rare congenital anomaly. Most patients may be asymptomatic, but some may experience major cardiac events such as syncope, arrythmias and sudden cardiac death. We present a 16-year old patient, who had several syncopes, with anomalous origin of right coronary artery from left coronary sinus, with an intramural and interarterial course between the pulmonary artery and the aorta. We describe a new surgical procedure of neo-ostium creation with saphenous vein.